SolarVision Almería: All-Sky Images - Yann Fabel; Niklas Blum; Bijan Nouri; Stefan Wilbert; Sergio Gonzalez Rodriguez; Luis Zarzalejo (PANGAEA, 2025)
This dataset provides ground-based image and sensor measurement data from a scientific research site in southern Spain (Tabernas, Almería). Its main contributions include all-sky images in the visible spectrum from three different fish-eye cameras capturing clouds motions, as well as diffuse, direct and global solar irradiance measurements from ISO 9060 class A spectrally flat pyrano- and pyrheliometers. The cameras and irradiance measuring devices are co-located within a radius of 20m at the same meteorological station. Image data is provided in its original resolution ranging from 4 to 8 MP depending on the camera, in 8-bit JPEG format. The dataset contains low-dynamic-range (LDR) images with fixed exposure times between 80 and 320μs. Furthermore, two cameras were temporarily configured to automatically generate high-dynamic-range (HDR) images. For one of the cameras, exposure series were captured, consisting of three sequential images with increasing exposure times.
In: Fabel, Y et al. (2025): SolarVision Almería: A Ground-Based Dataset of All-Sky Images, Solar Irradiance, and Meteorological Measurements [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.980067